واقع استخدام استراتيجيات التدريس من قبل المعلمين لتلاميذ ذوي الاعاقة الفكرية في مراكز التربية الخاصة في مركز محافظة اربيل - ياسين محمد افراح; عامر بدر الدين ايه (Journal of College of Education, 2020)
The aim of this research is to identify the most important instructional strategies used by teachers in special education centers for the mentally disabled and to identify the obstacles that stand in front of the teachers without using effective teaching strategies in the center of Erbil governorate. For the purpose research, the researcher used the descriptive method with a questionnaire to collect the data, andthe questionnaire consisted of two axes: the first to identify the teaching strategies and the second to identify the obstacles . The sample consist of (20) teachers ofthe Mental Retardation chose from all centers of special education in Erbil.The results found that the most important teaching strategies used by teachers with mental disabilities are the strategy of diction, mastery learning, programming learning, self-learning, educational games, conceptual maps, brainstorming. The least used strategy was the computer literacy strategy. As for the obstacles to teachers’ use of effective teaching strategies, the most important of these obstacles are the lack of university qualification in the preparation, implementation and evaluation of teaching strategies and methods, and the lack of training courses during the service in the use of appropriate strategies to teach people with mental disabilities and the lack of means and educational techniques required by the use of these strategies, And the lack of follow-up by the relevant educational supervisors from the Ministry of Education